Nutritional Needs of Dairy Cows: creation of an application for calculations - Adriano Medeiros Alves da Silva; José Crisólogo de Sales Silva (Universidade Estadual de Alagoas, 2021)
The NRC system determines the nutritional needs of animals based on standardized calculations according to the purpose of rearing and other animal data. However, not all breeders and many technicians have difficulty using this pattern correctly. This course conclusion work was developed with the objective of founding and executing the elaboration of an application for android that has as main functionality the calculation of the nutritional needs for dairy cows. Methodologically, the work was developed through bibliographic research to determine the criteria to be used in calculating the dietary needs of the animals chosen for the study. Then, based on the choice of the NRC as the basis for such calculations, an application was developed that can be installed and run on devices that have an android system and from the provision of data on the animals to be fed, the application presents as a result the nutritional needs. The possibility for the breeder to have a system at hand that facilitates the feeding of his flock contributes to greater profitability and quality of the breeding.